Molecular Genetic Basis of Collagen Used in Chronic Diabetic Wounds (Texas Journal of Medical Science, 2024)
The review of the world literature, is devoted to the role of collagen in the process of wound healing. The problems of epidemiology of chronic wounds and ulcers of various genesis, physiology and pathophysiology of wound healing phases are considered. The pathogenetic role of different types of collagen, as well as the mechanisms of collagen, macrophage, fibroblasts, matrix metalloproteinases and other cytokines in healing ulcers are discussed. The prospects of development and use of medical products and preparations based on collagen in the treatment of patients with chronic wounds and ulcers are shown. The results of clinical studies on the effectiveness of collagen with preserved (native) and unsaved (fractionated) structure are presented. The advantages of using native collagen in the treatment of diabetic foot syndrome are demonstrated